Teacher enthusiasm: a potential cure of academic cheating - Orosz, Gábor; Tóth-Király, István; Bőthe, Beáta; Kusztor, Anikó; Kovács, Zsuzsanna Üllei; Jánvári, Miriam (Frontiers in Psychology, 2015)
In this research we claim that teachers’ enthusiasm matters regarding student engagement in terms of academic cheating. Previous studies found that perceived enthusiasm of teachers is positively related to the intrinsic motivation of the students. However, it was less investigated how perceived enthusiasm is related to cheating. In the first exploratory questionnaire study (N = 244) we found that during the exams of those teachers who are perceived to be enthusiastic students tend to cheat less. In the second questionnaire study (N = 266) we took academic motivations into consideration and we found that the more teachers seem enthusiastic the cheating rate will be lower among university students. Aggregated teacher enthusiasm was positively related to intrinsic motivation, negatively related to amotivation, and not related to extrinsic motivation. Aggregated teacher enthusiasm was directly and negatively linked to cheating and it explained more variance in cheating than academic motivations together. These results suggest that teachers’ perceived enthusiasm can be a yet unexplored interpersonal factor which could effectively prevent academic cheating.